2007
DOI: 10.1002/rcm.3000
|View full text |Cite
|
Sign up to set email alerts
|

Fast and direct screening of polyaromatic hydrocarbon (PAH)‐contaminated sand using a miniaturized membrane inlet mass spectrometer (mini‐MIMS)

Abstract: A miniaturized membrane inlet mass spectrometer (mini-MIMS; total weight 10 kg everything included) was equipped with a small sample cell using a flat sheet silicone membrane mounted close to the ionizing region of a multipole mass spectrometer. Spiked sand samples were placed in small stainless steel vials and dropped into the heated sample cell (>150 degrees C). A hole in the vial in front of the membrane and above the sand made it possible for the polyaromatic hydrocarbon (PAH) residuals to penetrate the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…For example, SCIEX triple quadrupoles were introduced in the 1980s to address this very problem, e.g., the Mississauga disaster was monitored in this way [17], although these successful systems were transportable, not portable [18,19]. Several versions of portable mass spectrometers have been used for in situ gasphase chemical analysis [20,21] based on selective membrane sampling [22][23][24][25]. A related sorbent introduction system using preconcentration in a solid matrix and thermal release was employed to achieve trace level detection of benzene with the handheld Mini 10.5 [26].…”
mentioning
confidence: 99%
“…For example, SCIEX triple quadrupoles were introduced in the 1980s to address this very problem, e.g., the Mississauga disaster was monitored in this way [17], although these successful systems were transportable, not portable [18,19]. Several versions of portable mass spectrometers have been used for in situ gasphase chemical analysis [20,21] based on selective membrane sampling [22][23][24][25]. A related sorbent introduction system using preconcentration in a solid matrix and thermal release was employed to achieve trace level detection of benzene with the handheld Mini 10.5 [26].…”
mentioning
confidence: 99%
“…The homemade integrated hot cell membrane inlet/ion source system is very similar in design to the sample cell system that we introduced in 1998 for the analysis of flavor compounds directly from microbial media 26. A schematic diagram of the construction principles of our sample cells was shown in the original paper26 and a photograph showing the hot sample cell used recently for soil analysis has also been published 25. The major difference between the earlier sample cells and the present system is that the closed ion source is removed from the mass spectrometer and built into one side of a vacuum flange, whereas the sample cell is attached to the other side of the flange.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated that sand and soil samples can be directly and quantitatively analyzed for their content of polyaromatic hydrocarbons (PAHs) simply by inserting a sample vial with the contaminated sample into a hot (170°C) cell with a membrane interface to the electron ionization (EI) source of a mass spectrometer 25. The present paper explores the possibility of using the hot cell MIMS technique as a general tool for fast and direct screening of solid materials for their potential liberation of chemicals.…”
mentioning
confidence: 99%
“…However, the pressure of 10 À3 Pa inside the SPI source limited the sample input, and the limit of detection (LOD) of benzene was only 25 mg L À1 . Other types of membrane inlet have also been developed to improve the performance of on-line mass spectrometry, [13][14][15][16][17][18][19][20][21][22][23][24] such as the direct external probe hollow ber membrane (HFM), 25 the direct ow-through HFM probe, 13,26 the trap-and-release HFM, 15,21 the intermediate pressure region membrane and the single-side membrane etc.…”
Section: Introductionmentioning
confidence: 99%